Rooting for the Home Team : Sport, Community, and Identity - Nathan, Daniel A. (Book collections on Project MUSE., 2013)
This book examines how various American communities create and maintain a sense of collective identity through sports. Looking at large cities such as Chicago, Baltimore, and Los Angeles, as well as small rural towns, suburbs, and college towns, the contributors consider the idea that rooting for local athletes and home teams often symbolizes a community's preferred understanding of itself, and that doing so is an expression of connectedness, public pride and pleasure, and personal identity.